Air quality impacts of the 2019–2020 Black Summer wildfires on Australian schools. (15th September 2021) - Di Virgilio, Giovanni; Hart, Melissa Anne; Maharaj, Angela M.; Jiang, Ningbo
Abstract: The 2019–2020 Black Summer wildfires wrought destruction across Australia and exposed millions of people to air pollution. Using a new school-based observational network alongside long-standing observations, we provide the first assessment of spatiotemporal variations in Black Summer's air pollution impacts across Sydney, including how meteorology modulated the severity and timing of these episodes. Throughout the summer, hourly fine particulate matter (PM2.5 ) concentrations at schools often exceeded 25 μg m − ³ (i.e. the national daily average standard for PM2.5 ) for up to 8 h, with PM2.5 spikes frequently reverberating across Sydney, creating city-wide impacts. However, timing and magnitude varied markedly with location, and a geographic sequence of impacts was evident, reflecting smoke transport by the passage of synoptic features, especially pre-frontal troughs. Temperature, dew point temperature, and air pressure had significant, mainly positive non-linear associations with PM2.5, whereas negative relative humidity‒PM2.5 associations increased in strength at 70% humidity, and negative wind speed‒PM2.5 associations reversed at higher speeds reflecting increased synoptic-scale advection of PM2.5 . This study provides insights into the complex spatiotemporal variations in air pollution during wildfires and the corresponding influential meteorological factors. Together, these insights can inform improvements in air quality forecasting and support planning to reduce exposure to smoke emissions, thus increasing the preparedness requirements of society to mitigate the impacts of severe wildfires. Highlights: New school sensor network gives insights into PM2.5 pollution of Black Summer fires. Advection by pre-frontal troughs is a key driver of PM2.5 spatiotemporal variation. Humidity and temperature are the most consistent predictors of elevated PM2.5 Increased advection reverses negative wind speed-PM2.5 associations at high speeds. The PM2.5 pollution meteorology informs future fire resilience planning.